Policy deficiencies and contingency plans: groundwater management implications for baseflow contributions to the Colorado River - Perry, Denielle; Swanson, Riley K.; Springer, Abraham E. (Frontiers in Environmental Science, 2024)
The Colorado River is a vital water source for the western United States, yet the river is governed by disjointed and outdated policies that have left water management fragmented and water quantities overallocated. Groundwater is an overlooked component of Colorado River Basin (CRB) water supplies, making it vulnerable to overuse from disparities in uncoordinated protective management strategies. In this study, we analyzed state level groundwater policies to reveal the diversity and efficacy of groundwater governance mechanisms. The existence existing of groundwater management plans for each state throughout the basin is are fragmented and limited in scope. We found that with policies only covering 22% of the basin, they do not provide adequate protection at the basin scale for the sustainable use of groundwater resources in the face of increasing demands, creating a positive feedback loop that reinforces the scarcity issue. We conclude that a comprehensive management plan that can fully address resource use throughout the CRB is necessary for the sustainable use of groundwater and its contribution to base flow in the Colorado River. We suggest that such a plan could be derived through an interstate compact like the Colorado River Compact that is used for surface water management.